1997
DOI: 10.2307/4450288
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Environments & Student Outcomes in Senior High School Biology

Abstract: NTERNATIONAL research efforts involving the conceptualization, assessment and investigation of perceptions of psychosocial aspects of the classroom environment have firmly established classroom environment as a thriving field of study (see reviews by Fraser 1994; Fraser & Walberg 1991). For example, recent classroom environment research has focused on constructivist classroom environments (Taylor, Fraser & White 1994), computer-assisted instruction classrooms (Teh & Fraser in press), and teacher-student interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Finally, the results suggest consistent relationships between the perception of the behavior of the teacher and self-regulation of the learning, in line with studies that describe a positive relationship between the profi le of the teacher and academic and emotional dimensions of the students (Brekelmans, 1989;Brekelmans, Wubbels, & Levy, 1993;Henderson, Fisher, & Fraser, 1994;Brok, 2001). Data from this study revealed a positive relationship between the self--regulation of learning and the perception of Leadership, Helpful/Friendliness and Understanding, as well as a negative relationship between self-regulation of learning and the perception of Uncertainty, Dissatisfaction and Admonishment, which indicates the positive infl uence of the behavior of the Mathematics teacher guided by greater Proximity and Infl uence on the self-regulation of learning of the students.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, the results suggest consistent relationships between the perception of the behavior of the teacher and self-regulation of the learning, in line with studies that describe a positive relationship between the profi le of the teacher and academic and emotional dimensions of the students (Brekelmans, 1989;Brekelmans, Wubbels, & Levy, 1993;Henderson, Fisher, & Fraser, 1994;Brok, 2001). Data from this study revealed a positive relationship between the self--regulation of learning and the perception of Leadership, Helpful/Friendliness and Understanding, as well as a negative relationship between self-regulation of learning and the perception of Uncertainty, Dissatisfaction and Admonishment, which indicates the positive infl uence of the behavior of the Mathematics teacher guided by greater Proximity and Infl uence on the self-regulation of learning of the students.…”
Section: Discussionsupporting
confidence: 70%
“…Often. This questionnaire has been validated in numerous countries (Fisher, Henderson and Fraser 1997;Fraser, Giddings and McRobbie 1995;Fraser and Lee 2009;Lightburn and Fraser 2007;Wong and Fraser 1995).…”
Section: Learning Environmentsmentioning
confidence: 99%
“…Empirical evidence shows that psychosocial dimensions of the classroom environment are strong predictors of student outcomes across a range of subject areas of the formal school curriculum. Previous studies conducted in science classrooms have established consistent and convincing support for the predictive validity of student perceptions of the classroom leaming environment in accounting for appreciable amounts of variance in student cognitive outcomes and attitudes toward science (Fisher, Henderson & Fraser, 1997;McRobbie & Fraser, 1993). In Singapore, Wong and Fraser (1996) employed the Science Laboratory Environment Inventory to establish positive associations between student cohesiveness, integration, rule clarity, and material environment in chemistry classes and students' attitudes toward chemistry.…”
Section: The Field Of Classroom Environment Researchmentioning
confidence: 95%